The practical roadmap for peri-cystectomy approaches in muscle-invasive bladder cancer - Kattan, Joseph; Kattan, Clarisse; Aoun, Fouad; Nemr, Elie (Frontiers in Oncology, 2025)
The management of muscle-invasive bladder cancer (MIBC) remains a challenging topic since it is witnessing rapidly evolving changes and new drug approvals. In fact, more effective approaches are now available to improve the outcomes of patients with MIBC who are candidates for cystectomy. Neo-adjuvant cisplatin-based chemotherapy was the standard approach for patients who were deemed cisplatin-eligible. Also, adjuvant cisplatin-based chemotherapy was considered for high-risk operated patients who did not receive the standard neo-adjuvant chemotherapy. It was only recently that adjuvant immune checkpoint inhibitors were proved effective in adjuvant settings and were approved for high-risk MIBC patients after neo-adjuvant chemotherapy followed by cystectomy or for those who did not receive neo-adjuvant chemotherapy and were not eligible for adjuvant cisplatin-based chemotherapy. More recently, adding immune checkpoint inhibitors to neo-adjuvant chemotherapy and to post-cystectomy adjuvant therapy seemed to be very promising. In this review article, all current peri-cystectomy options are briefly described with an attempt to guide and simplify choices by drawing a roadmap covering all the practical scenarios.